Genetic analysis for various agromorphological and quality traits in bread wheat (Triticum aestivum) - KUMAR, SANDEEP; KUMAR, PRADEEP; KERKHI, S A; SINGH, GYANENDRA (The Indian Journal of Agricultural Sciences, 2017)
A study was made to estimate gene action and combining ability effects involving 10 diverse parents and their 45 F1s (half diallel approach) developed and evaluated during 2012-13 and 2013-14 crop seasons, respectively. The general combining ability (GCA) estimates for bread wheat (Triticum aestivum L.) genotypes namely, HD 2967 (days to maturity, plant height); DBW 90 (plant height, spikelets/spike, grains/spike, grain yield); HD 2824 (plant height, spikelets/spike); HD 3095 (spikelets/spike, grains/spike, grain yield); and HD 2733 (plant height, days to maturity and grains/spike) showed favourable GCA effects. Estimates of specific combining ability (SCA) effects revealed that cross combinations DBW 90 × HD 2733, HD 3095 × RAJ 4246, PBW 435 × HD 2824, PBW 435 × RAJ 4246 and HD 2967 × RAJ 4246 showed high and significant SCA effects, and thus might be exploited through heterosis breeding to improve these traits. Significant values of additive (D) and dominance (H1) variance for six traits (plantheight, grains/spike, spikelets/spike, 1000-grain weight, gluten content and grain yield) indicated that expression of these traits is controlled by both additive and non-additive type of gene action. Positive and significant values of h2 for plant height, grains/spike, spikelets/spike, 1000-grain weight and grain yield; indicated preponderance of dominance component. Average degree of dominance (H1/D)1/2 was more than unity in most of the F15 for grains/spike, spikelets/spike, 1000-grain weight, gluten content and grain yield, thereby indicating the preponderance of over-dominance gene action. Positive and significant values of F-test indicated the preponderance of dominance and positive genesin the expression of these traits. The proportionate distribution of dominant and recessive alleles indicated presence of dominant alleles in the parents. Regression analysis indicated that days to maturity, plant height, grains/spike, 1000-grain weight, gluten content and grain yield were governed by dominance gene action. Genotype HD 3095 contained maximum dominant genes for days to maturity, spikelets/spike; while HD 2967 for plant height, grains/spike, 1000-grain weight and HD 2824 for gluten content and grain yield that thus these could be utilized as donorsfor bi-parental mating or diallel selective mating system for improvement in these traits.